Properties and Applications of Neutrosophic Burr XII Distribution - Laila A. Al-Essa; Farrukh Jamal; Shakaiba Shafiq; Sadaf Khan; Qamer Abbas; Rehan Ahmad Khan Sherwani; Muhammad Aslam (International Journal of Computational Intelligence Systems, 2025)
Abstract Primarily, when the hazards function has intricate structures, the BrXII distribution is an established framework for lifetime data analysis. However, classical probability models are limited in the sense that they cannot measure or record the data in exactness fueling the notion of indeterminacy in data collection process. This study addresses this issue by proposing the idea of neutrosophic BrXII (NeS-BrXII) distribution. The primary objective is to study the statistical properties of the proposed model by providing explicit expressions of reliability properties, the expression of moments and generating function, expression of order statistics, mean residual life, mean inactivity time, stochastic ordering, income inequality measures, and entropy in neutrosophic realm. In addition, the neutrosophic model parameters are estimated using the principle of maximum-likelihood estimation. Further, the precision of these model estimates is verified via a simulation study of the proposed model. Applying the model on two real-world material sciences data sets reinforces its efficacy with the NeS-BrXII distribution proving to be more suitable for managing anomalies in neutrosophic surface analysis among other models.